A review of the Sarcophaga (Heteronychia) (Diptera: Sarcophagidae) of Sardinia - Whitmore, Daniel (Zootaxa, 2009)
An account is given of the species of Sarcophaga Meigen, 1826 subgenus Heteronychia Brauer & Bergenstamm, 1889 known from the island of Sardinia (Italy). Most of the nearly 1,400 specimens examined were collected in the SW part of the island during 2003–2006 as part of a project investigating the arthropod diversity of the Monti Marganai and Montimannu areas (respectively Carbonia-Iglesias and Medio Campidano provinces). The study resulted in the finding of eight species of Heteronychia, six of which are recorded from Sardinia for the first time. Sarcophaga (Heteronychia) penicillata Villeneuve, 1907, previously mentioned in the literature, is excluded from the fauna of the island. Sarcophaga (Heteronychia) thirionae (Lehrer, 1976) is recorded for the first time from Europe and North Africa (Algeria). One species, Sarcophaga (Heteronychia) gabrielei sp. nov., from various sites in the limestone massif of Marganai, is described as new. Previously unpublished records from other Italian regions and from other countries (Algeria, Canary Islands, Greece) are also given for several species. Sarcophaga (Heteronychia) schnabli Villeneuve, 1911 is recognized as a junior synonym of S. (H.) consanguinea Rondani, 1860 syn. nov. The possible synanthropy of Sarcophaga (Heteronychia) pandellei (Rohdendorf, 1937) is briefly discussed. A key to males and females of all known Sardinian and Corsican species of Sarcophaga (Heteronychia) is provided.